Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1177/1545968308317431
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes Can Vary by Dose: Learning-Based Sensorimotor Training for Patients Stable Poststroke

Abstract: Learning-based sensorimotor training based on the principles of neuroplasticity was associated with improved function in patients stable poststroke. The gains were dose specific with the greatest change measured in subjects participating in the high-intensity treatment group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 19 publications
0
74
0
Order By: Relevance
“…Increased exposure to novel therapy methods has, however, produced inconsistent results, with reports of positive dose-response effects (learning-based sensorimotor training [35]), no effect of increased dose (neuromuscular electrical stimulation [36]), and an inverse response to higher dose interventions (constraint-induced movement therapy [CIMT] [36]). The latter result raises the possibility of a limit on the amount of RA training that is beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Increased exposure to novel therapy methods has, however, produced inconsistent results, with reports of positive dose-response effects (learning-based sensorimotor training [35]), no effect of increased dose (neuromuscular electrical stimulation [36]), and an inverse response to higher dose interventions (constraint-induced movement therapy [CIMT] [36]). The latter result raises the possibility of a limit on the amount of RA training that is beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the conventional therapy group were given a booklet of tabletop exercises for home therapy of the hand developed by experienced occupational therapists and implemented in a prior clinical trial [42] and were instructed on how to correctly perform each hand exercise (see Appendix, available online only). Both groups were asked to perform self-guided therapy for at least 3 h/wk over at least three sessions per week, for three consecutive weeks, for a total of 9 h of therapy; such a dose had been found previously to be sufficient to induce significant improvements in hand movement ability [8,[43][44][45]. Both groups were also asked to manually record the amount of time they spent performing their self-guided therapy on a written exercise log.…”
Section: Interventionsmentioning
confidence: 99%
“…Intensive movement practice can reduce hand impairment [2][3][4][5][6], but issues such as cost and access may limit the dose of rehabilitation exercise delivered one-onone with a therapist. Because of these and other factors, most individuals do not perform the large number of exercise repetitions required during therapy to maximize recovery [7][8]. Home-based rehabilitation programs may be prescribed after stroke with the intent to increase the amount of rehabilitation exercise individuals perform.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the recovery mechanism after brain damage can be viewed as a process induced by exercise training. Previous studies have reported that higher intensity and activeassisted mode of the robot-assisted therapy movement may lead to better improvement in motor function (30,34,35). Upper extremity training in patients with stroke using the Neuro-X® provides an environment that allows suitable training of each patient using the maximum remaining muscle strength of the affected arm.…”
Section: Discussionmentioning
confidence: 99%